Warehouse Management System for Smart Digital Order Picking Systems - Dina Fitria Murad; Widya Ratnasari; Bhumyamka Yala Saputra; Bambang Dwi Wijanarko (IJNMT (International Journal of New Media Technology), 2019)
The purpose of this paper is to identify problems in the identified picking process that lead to consumer dissatisfaction and provide solutions to problems that exist in the company, especially in warehousing, supported by analysis of the running system to obtain the information needed. The decision-making system is used to be able to produce information regarding picking orders in adjusting the number of orders, availability of pickers and distribution to consumers. The research method that uses the PIECES analysis and technology acceptance model method to determine the user's acceptance of the system being built. The smart digital order picking system was able to significantly accelerate the order picking business process from the ones that previously took a long time after implementation could meet consumer needs quickly.